Mitos Gendhing dalam Upacara Bersih Dusun Dalungan, Kelurahan Macanan, Kecamatan Kebakkramat, Kabupaten Karanganyar - Dewi, Ita Puspita (Sorai: Jurnal Pengkajian dan Penciptaan Musik, 2019)
This paper, entitled “Gendhing Myth in the Bersih Dusun Ceremony in Dalungan, Macanan, Kebakkramat, Karanganyar” started from the writer's interest in seeing the socio-cultural phenomenon that has become an annual tradition for Dalungan Hamlet residents. This study aims to uncover the gendhing posted by the community in the bersih dusun ceremony of the Dalungan hamlet. The myth of Gendhing is inseparable from the factors that influence the existence of sacred values related to the rite. The magical value that exists in the Gendhing is based on the cultural belief system of Javanese actors and other supporting elements of ritual such as folklore and cultural values inherited from the ancestors. The myth of Gendhing must also be supported by the presence of dhanyang and also the pundhèn caretaker, as well as community leaders such as the RW leader, RT leader, Dalungan elders, and the entire Dalungan community. This research uses qualitative research methods, including observation, data collection, data analysis, data presentation, and conclusions. This research uses P.S Hary Susanto's myth theory which explains the myths according to Mercia Eliade's thought,  which is to solve problems related to the myths of Javanese cultural society and the myth of Gendhing in the clean ritual of the Dalungan hamlet.